Physicochemical and functional properties of yogurt enriched with ultrafiltered juice of Red Prickly Pear (Opuntia ficus-indica) as a functional ingredient - Alondra Valadez Pineda; Gerardo Mendez Zamora; Nydia Corina Vasquez Aguilar; Luisaldo Sandate Flores; Carlos Alberto Hernandez Martinez; Sugey Ramona Sinagawa Garcia (Tecnociencia Chihuahua)
Yogurt has long been recognized as a health-promoting food for its bioavailability of protein, energy, probiotics and calcium, increasing digestibility, as well as preventing potential diseases beyond basic nutritional function. Recently, yogurt has become one of those foods whose functional properties are developed by adding functional substances with a potential positive effect on health. The objective was to evaluate the effect of ultrafiltered juice of red fruits of O. ficus-indica as a functional ingredient in yogurt. A completely randomized block design (CRBD) was used. The treatments were: yogurt with 0 % ultrafiltered red prickly pear juice (Y0) as a control; yogurt with 10 % ultrafiltered red prickly pear juice (Y1); yogurt with 20 % ultrafiltered red prickly pear (Y2); and yogurt with 30 % ultrafiltered red prickly pear juice (Y3). The variables to measure in each yogurt treatment were pH during lactic fermentation and the final product, syneresis, energy content, colorimetry, composition (total solids, protein, fat and ash), antioxidant activity (DPPH, ABTS and FRAP), phenol content and sensory evaluation. The incorporation of red prickly pear ultrafiltrates accelerated antioxidant activity and total phenolic contents. Finally, the sensory panel satisfactorily accepted the incorporation of red prickly pear ultrafiltered in yogurt.